Reproductive problems in water buffalo cows associated with non-diagnosed genital lepto- spirosis. Preliminary results - Rosaura Pérez-Gil (Revista Científica)
Leptospirosis in female buffaloes can cause abortions, fetal death, premature calving, and the birth of weak and/or underweight calves; however, sub-fertility and early embryonic death have been little studied. In addition, it is not completely understood whether these reproductive problems are associated with the persistence of the bacteria in the reproductive tract. The main goal of this research is to demonstrate the presence of the bacterium Leptospira spp. in the genitourinary tract of Bubalus bubalis females. For this, samples of 25 females from 4 farms with poor reproductive performance were brought to a slaughterhouse, and samples of uteri, oviducts, ovaries, and kidneys were collected. Fresh tissue samples were cultured in the liquid Ellinghausen–McCullough–Johnson–Harris medium (EMJH), a selective medium for Leptospira. In addition, tissue samples were prepared for histological analysis by fixation in a 10% buffered formaldehyde solution and stained with hematoxylin and eosin. PCR was performed on nine culture samples for identification of Leptospira spp., by using two pairs of primer for the markers, G1-G2 derived from a sequence from the genomic library of L. interrogans serovar icterohaemorragiae, strain RGA, which was described by Gravekamp et al. (1993) and Internal 1 and Internal 2 derived from the sequence of the gene encoding the LipL32 protein and specific to identify pathogenic Leptospira, described by Haake et al. (2000). The reproductive efficiency of the farms was characterized by prolonged days open and calving intervals (average of 307 and 587 days, respectively). In addition, the abortion rate averaged 40%, and the occurrence of hemoglobinuria, jaundiced vaginal mucosa, and congestive vaginal mucosa were 32%, 16%, and 24% respectively. The histological examination revealed uterine fluid (68%), uterine fibrosis (48%), chronic non-suppurative endometritis in 68%, severe glandular atrophy in 44%, and hemorrhage in the perimetrium in 60%. In oviducts, fibroplasia was observed in 52% of samples and salpingitis in 32%, while in kidneys, chronic interstitial nephritis was observed in 56% of samples. At the ovary level, 16% of follicular cysts, 20% of atrophy, and persistent corpus luteum in 28% were observed. The tissue culture was positive for Leptospira spp. in the following percentages: uterus 76%, ovary 84%, oviduct 88%, and kidney 96%. PCR using the marker G1-G2 revealed the presence of Leptospira DNA in 55.5% of uterus, ovary, and oviduct samples, and 44.4% of kidneys; and using the primer Internal 1 and 2 identified pathogenic Leptospira spp, in 55.5% of the uterus and kidney samples, 33.3% in ovaries and 66.6% oviduct. These results show reproductive problems in female buffaloes associated with genital leptospirosis. These findings suggest the need to develop new approaches for diagnosing this pathology using molecular techniques and bacterial cultures, as well as the evaluation of new prophylactic and therapeutic alternatives to avoid the colonization of the reproductive tract.